2005
DOI: 10.1103/physrevlett.94.195503
|View full text |Cite
|
Sign up to set email alerts
|

New Helical Chain Structure for Scandium at 240 GPa

Abstract: X-ray diffraction experiments were carried out at 297 K in order to study structural-phase transitions of the trivalent rare-earth metal scandium (Sc) at pressures of up to 297 GPa. Four stages of structural transition were observed around 23, 104, 140, and 240 GPa. The crystal structure of the highest-pressure phase, Sc-V, was found to be a hexagonal lattice (S.G.: P6(1)22 or P6(5)22) consisting of 6-screw helical chains. The lattice can be derived from modulations of the interplane stacking of the (111) plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
64
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(69 citation statements)
references
References 20 publications
5
64
0
Order By: Relevance
“…Sc falls somewhat out of line since it transforms at ∼ 23 GPa from the hcp to an incommensurate host-guest structure [30,31] instead of to the canonical Sm-type structure. In fact, recent X-ray diffraction experiments on Sc to 297 GPa reveal four successive structure changes, the final being to a new helical chain structure above 240 GPa [32]. It has been suggested that the differences between Sc and the other trivalent d-electron metals may arise at least in part from the changes in electronic structure associated with the complete absence of delectrons in Sc's ionic core, thus allowing its 3d valence electrons to penetrate further into the core region (no orthogonality condition) and thus to assume a higher degree of localization [33,34].…”
Section: Resultsmentioning
confidence: 99%
“…Sc falls somewhat out of line since it transforms at ∼ 23 GPa from the hcp to an incommensurate host-guest structure [30,31] instead of to the canonical Sm-type structure. In fact, recent X-ray diffraction experiments on Sc to 297 GPa reveal four successive structure changes, the final being to a new helical chain structure above 240 GPa [32]. It has been suggested that the differences between Sc and the other trivalent d-electron metals may arise at least in part from the changes in electronic structure associated with the complete absence of delectrons in Sc's ionic core, thus allowing its 3d valence electrons to penetrate further into the core region (no orthogonality condition) and thus to assume a higher degree of localization [33,34].…”
Section: Resultsmentioning
confidence: 99%
“…3b) [25,26]. Whereas no T c (P ) data is available across the I→II boundary, T c is seen to drop sharply at the II→III boundary and then rise slowly as the pressure is increased further.…”
Section: Sc Metalmentioning
confidence: 99%
“…Whereas in Lu T c increases monotonically with pressure to 12.4 K at 174 GPa, in Sc T c increases rapidly with pressure, reaching a maximum value of 19.6 K at 107 GPa in the Sc-II phase. If the pressure is increased further, Sc-II transforms to Sc-III [25,26] whereupon T c drops to 8.31 K at 111 GPa. Sc possesses with 19.6 K the second highest value of T c of any elemental superconductor.…”
Section: Introductionmentioning
confidence: 99%
“…But the magnitude of the effect seems improbably large, noting that the spacing of 1.957 Å at 101 GPa is even smaller than the closest contact distance of 2.052͑2͒ Å in Sc-V at the very much higher pressure of 242 GPa. 10 In this paper we propose a different incommensurate composite solution. It has the same host structure but a guest component that has a larger spacing along the c axis and is C-face-centered rather than body-centered, isostructural with Sr-V rather than Bi-III.…”
mentioning
confidence: 99%